POLA KOMUNIKASI KEPALA MADRASAH DALAM MEMBANGUN MOTIVASI KERJA GURU DI MTSN 3 TABALONG - Chairul Echwan (CV. ADIBA AISHA AMIRA, 2024)
This research is motivated by the problem of the need to build teacher work motivation in order to encourage the achievement of good performance quality in madrasahs. One of the factors that can build teacher work motivation is the application of the madrasah principal's communication pattern. This problem is also a major concern for the Principal of MTsN 3 Tabalong to be able to apply an effective communication pattern in building teacher work motivation in MTsN 3 Tabalong. In this case, the five laws of effective communication, namely respect, empathy, audible, clarity, and humble, are the standard measurements in determining the development of teacher work motivation in MTsN 3 Tabalong. The purpose of this study was to find out about the communication pattern of the madrasah principal in building teacher work motivation in MTsN 3 Tabalong. The type and approach used in this study is a descriptive research type and uses a qualitative approach. The object of this study is the communication pattern of the Madrasah Principal at MTsN 3 Tabalong in building teacher work motivation and the subjects of the study are the madrasah principal and teachers of MTsN 3 Tabalong. Furthermore, data collection techniques were carried out by means of observation, interviews and documentation. Then the data analysis was carried out in three stages including data reduction, data display and verification. The results of the study obtained were that the communication pattern of the Principal of MTsN 3 Tabalong had been carried out by implementing the five laws of effective communication, namely respect, empathy, audible, clarity, and humble. So that it can provide an impact in the form of a pleasant work environment, a sense of comfort, self-confidence, openness, the growth of a high sense of sympathy and then can build teacher work motivation. Thus, the communication pattern of the Principal of MTsN 3 Tabalong can be said to be running well and effectively. Furthermore, the building of teacher work motivation can also be seen from the evidence of the teacher attendance list which shows the active and disciplined presence of teachers.